2014
DOI: 10.7556/jaoa.2014.178
|View full text |Cite
|
Sign up to set email alerts
|

Laser Doppler Flowmetry in Manual Medicine Research

Abstract: Laser Doppler flowmetry (LDF) is commonly used in combination with reactivity tests to noninvasively evaluate skin sympathetic nerve activity and skin microvascular function. In manual medicine research, LDF has been used as a marker for global peripheral sympathetic nervous system function, but these results should be considered with caution because skin sympathetic nerve activity physiology is often overlooked. Another limitation of LDF in manual medicine research is the processing of LDF recordings. Two met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…As has extensively been reported in the literature, little useful information can be gleaned from directly examining LDF signals . Consider the BF signals shown in Figure A,B recorded from skin at the forearm of two different people with and without T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…As has extensively been reported in the literature, little useful information can be gleaned from directly examining LDF signals . Consider the BF signals shown in Figure A,B recorded from skin at the forearm of two different people with and without T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study showed finger microcirculation, as detected by LDF, increases following 3 days of iloprost infusion but vanishes within 7 days in patients with systemic sclerosis, suggesting a longer lasting vasodilatory regimen remains to be established [10]. LDF has also been proposed as an indicator for sympathetic nervous system function [11][12][13][14][15]. In clinical scenarios, LDF and other tools have been used to measure microcirculation of certain diseases with abnormal neural/sympathetic modulation, such as segmental vitiligo [16][17][18] and port-wine stain [19,20], to diagnose these diseases or predict their response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is substantial evidence that microvascular changes occur very early and may play a role in their pathogenesis and progression [10]. In this context, it is impossible to ignore the modern methods of endothelial and micro-circulation assessment, such as LDF, which have a recognized clinical value [11]. The LDF method has some limitations resulting from the sensitivity of the results to various external measurement conditions, individual and local variability of blood flow in microcirculation; therefore, measurements should be standardized through the use of so-called provocation tests, most often causing local tissue hyperaemia [12].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the LDF PORH study are influenced by numerous factors, including NO release, endothelium dependent hyperpolarization [14], and shear stress [15]. According to Yvonne-Tee et al, ML and TM are the most reproducible parameters of the PORH method [16], and according to Zegar-Parodi, more reproducible results are obtained on the fingertips than on the forearm [11].…”
Section: Discussionmentioning
confidence: 99%